Therapeutic management of closed central slip injuries: Outcome of a service evaluation. (March 2019) - Capon, Annie; Watson, Alexander; England, Holly
Introduction: Closed central slip injuries can be difficult to manage and there is a lack of published research to support evidence-based clinical decision making in practice. This article presents the results of a service review in a busy trauma hospital hand therapy department. Method: Following a literature review and retrospective review of outcomes, new clinical guidelines for central slip injuries were developed. These were implemented with 22 patients referred to hand therapy for conservative management of closed central slip injuries during a one-year period. Results: The majority of patients (72%) had either an excellent or good outcome using the Strickland-Glogovac outcome measure and an average total active motion of 90% compared to their unaffected hand. Conclusions: The outcomes following implementation of new treatment guidelines following the service review are in line with the small amount of published data currently available. They provide detailed guidelines for the conservative management of closed central slip injuries in a busy out-patient setting.